A Comparison of Eckhart's Nothingness and Laozi's Wu - LI Yi, (Journal of Research for Christianity in China (JRCC), 2025)
Eckhartian studies have initiated a new round of dialogue between religious philosophy and comparative philosophy. The path of negation is a shared intellectual theme between Eckhart and Laozi, both of whom exhibit a particular affinity for nihil or the void. This paper compares Eckhart's nihil and Laozi's wu from two perspectives: God/Creator as pure nihil and the purity of nihil versus wu as the balanced opposite of yu's alienation, alongside explicit intellect and implicit knowledge. Correspondingly, the discussion proceeds as follows: Part One addresses the purity of Eckhart's pure nihil and Laozi's wu—imbued with chaos and mutually generating with yu; Part Two compares Eckhart's original insight—Paul's vision of God as nothingness—with Laozi's concept of the unseen: Following Eckhart's framework linking nothingness, seeing, and knowing, we explore parallels with Laozi's understanding of knowledge (ignorance and non-knowing) as part of this comparative series.
Keywords: Eckhart, Laozi, Nothingness